Prevalence and predictability of domestic violence against Iranian women - Mohammad Arshadi Bostanabad; Fariba Vaseai; Hossein Ebrahimi; Hossein Namdar Areshtanab (Cukurova Medical Journal, 2019)
Purpose: Domestic violence against women is a common hidden problem worldwide. Previous studies showed that it provides severe physical and psychological health problems for them. In addition, it imposes many costs to the health system of countries. The identification of risk factors of domestic violence is the first step of strategy for its managing and preventing. The purpose of this study is determined the prevalence and chronicity of domestic violence and its relationship with socio-demographic characteristics of women who refer to Health Centers.Materials and Methods: This cross-sectional descriptive study was conducted on 547 women referring to Health Centers. Sampling was done in the conventional method and data collection tools were demographic and CTS2 questionnaire.Results: Most of the participants (98.5%) had experienced violence in a past year. The highest and lowest of violence was the dimension of negotiation (97.7%) and injury (10.5%) respectively. The family income sufficiency, marital satisfaction was an important predictor for domestic violence against women.Conclusion: Domestic violence had a high prevalence. Empowering of the staff of Health Centers, using standard screening tools and preventive interventions are recommended.